2007
DOI: 10.1123/jsr.16.2.143
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Resistance Training Program in Multiple Sclerosis Spanish Patients: A Pilot Study

Abstract: Context:Physical exercise is regarded as a useful tool in the treatment of multiple sclerosis (MS). Generally, physical rehabilitation have been based on the prescription of aerobic exercises, while fewer programs have been aimed at developing muscular strength.Objective:To establish whether the physical fitness of MS sufferers can be improved by a training program for developing muscular strength.Design:Before and after studySetting:University multipurpose roomParticipants:36 patients, all able to walk, belon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
(30 reference statements)
0
9
0
3
Order By: Relevance
“…In all people, but more obviously in PwMS, having adequate levels of strength in the lower limbs is fundamental for walking, balance, and the autonomy of the patient [32]. This is one of the reasons why rehabilitation and physical conditioning of these patients is currently focused on strength training of the lower extremities [4,[32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…In all people, but more obviously in PwMS, having adequate levels of strength in the lower limbs is fundamental for walking, balance, and the autonomy of the patient [32]. This is one of the reasons why rehabilitation and physical conditioning of these patients is currently focused on strength training of the lower extremities [4,[32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that exercise and physical activity can reduce symptoms, increase cardiopulmonary health and improve quality of life for people with multiple sclerosis (pwMS) [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Physical disability is common in pwMS because multiple sclerosis (MS) exacerbations and disease progression result in secondary impairments, such as diffuse muscle weakness and poor cardiovascular fitness [15].…”
Section: Introductionmentioning
confidence: 99%
“…Coupled with low exercise self-efficacy [16,17], fear of exercising and high levels of fatigue, physical disability can lead to a progressively sedentary lifestyle [18]. Many studies have examined the effectiveness of physical exercise provision and behaviour change interventions to increase the adherence for people with MS in a laboratory-based or health providerbased clinic [3,[11][12][13][14][19][20][21][22][23], but few studies have explored exercise/physical activity participation and adherence in a home setting. Barriers to physical activity participation for many [24], particularly those living in rural areas [24][25][26], include dependence on experienced rehabilitation specialists [27], transport and service delivery high costs [28] and issues of limited accessibility to health-promoting practices.…”
Section: Introductionmentioning
confidence: 99%
“…ción, realizando un entrenamiento de 10-15 repeticiones máximas, el cual mostró un aumento significativo del la fuerza en ambos miembros. Estudios como los de Fimland et al (2010), Medina-Pérez et al (2014) o Pérez et al (2007) observaron diferencias significativas en la fuerza muscular de sus participantes, utilizando otros programas de entrenamiento diferentes a los de este estudio, como bandas elásticas o trabajo isométrico. Aunque todos los estudios están desarrollados en un periodo de entre 6 y 12 semanas de entrenamiento, no todos obtienen resultados satisfactorios en la medición de la fuerza como es en el caso de dos estudios (De Souza-Teixeira et al, 2011;Sabapathy et al, 2011) en el que no se encontró diferencias significativas en la fuerza muscular, pero si en la funcionalidad de los participantes.…”
Section: Fuerzaunclassified
“…En el presente estudio, en la medición del equilibrio se puede observar una tendencia a empeorar la estabilidad, sin saber con certeza si esto puede ser indicativo del entrenamiento de fuerza, o debido a las elevadas temperaturas climatológicas que hubo durante las mediciones del post, ya que debido a la sintomatología que tiene las personas con esclerosis múltiple afectan directamente a su movilidad. En cambio, haciendo mención del estudio de Pérez et al (2007), obtiene resultados similares a los de la presente investigación, al no observar diferencias significativas entre el pre y post-test en la medición del equilibrio. Por lo tanto, quizás fuese necesario añadir al programa de entrenamiento ejercicios aeróbicos o propios del equilibrio para la mejora de este.…”
Section: Equilibriounclassified